2021
DOI: 10.1093/cz/zoab059
|View full text |Cite
|
Sign up to set email alerts
|

Hematological parameters of a Neotropical wild frog population, with a phylogenetic perspective on blood cell composition in Anura

Abstract: Hematological parameters can provide key information to an animal health status. However, this information is usually hard to obtain. Here, we described hematological parameters of Leptodactylus podicipinus in the Brazilian Pantanal. We measured red blood cell morphometrics, erythrogram, and leukogram. We also tested for phylogenetic signal in erythrogram and leukogram of 48 frog species from 15 families, testing if body size explains their variation. Lymphocytes were the most abundant leukocytes (> 60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…In this study, five types of leukocytes: neutrophils, eosinophils, basophils, monocytes and lymphocytes were observed respectively in tiger frog peripheral blood, which was in accord with those described in neotropical wild frog ( Leptodactylus podicipinus ) ( Franco-Belussi et al, 2021 ), American bullfrog and African clawed frog ( Bricker, Raskin & Densmore, 2012 ), while most of fish lack basophils ( Fang et al, 2014 ; Zheng et al, 2015 ). The morphology of neutrophils, eosinophils and basophils in tiger frogs were usually round, which was consistent with those of other reported amphibians and mammals ( Salakij et al, 2005 ; Prihirunkit et al, 2007 ; Gutierre et al, 2008 ; Bricker, Raskin & Densmore, 2012 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, five types of leukocytes: neutrophils, eosinophils, basophils, monocytes and lymphocytes were observed respectively in tiger frog peripheral blood, which was in accord with those described in neotropical wild frog ( Leptodactylus podicipinus ) ( Franco-Belussi et al, 2021 ), American bullfrog and African clawed frog ( Bricker, Raskin & Densmore, 2012 ), while most of fish lack basophils ( Fang et al, 2014 ; Zheng et al, 2015 ). The morphology of neutrophils, eosinophils and basophils in tiger frogs were usually round, which was consistent with those of other reported amphibians and mammals ( Salakij et al, 2005 ; Prihirunkit et al, 2007 ; Gutierre et al, 2008 ; Bricker, Raskin & Densmore, 2012 ).…”
Section: Discussionsupporting
confidence: 88%
“…We only collected males due to the sampling strategy employed, which used acoustic signals to locate individuals. Previous studies found negligible differences between sexes in terms of haematological parameters ( Franco-Belussi et al, 2022 and references cited therein).…”
Section: Methodsmentioning
confidence: 83%
“…5 ). The model explained a substantial amount of variance (Nagelkerke's R 2 = 0.67), with site individually explaining 62.63% of the variance, while age explained 37.37% (see Franco-Belussi et al, 2023 ). The overall mean (±SD) of abnormalities in the urban (6.09 ± 2.47) was twice larger than in the rural population (3 ± 1.70).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations